The Use of Temporal Deixis in Portraying Time Displacement and Sequences of Event in Short Stories - Hajar Hujjatul Muthmainah; Oktiva Herry Chandra (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
This thesis deals with how readers understand the sequences of event and time displacement in the literary works especially short story. Temporal deixis, as one of deixis types, have an important role along with tense to help readers understand the story. This thesis identifies the sequences of event, describes time displacement and sequence event in short story by using temporal deixis and tense, and explains the use of temporal deixis in short stories. The result shows that four selected short stories contain temporal deixis and change of tense. In conclusion, the four selected short stories contain temporal deixis and change of tense to signify time displacement from present to past and vice versa.Keywords: temporal deixis; time displacement; sequences of event; tense; short story